Anxiety. - Art Focus Contemporary Israeli Art, Jerusalem 1994 (Ramat-Gan : The Museum of Israeli Art, 1994)
Uri, Aviva ; Ben-David, Arnon ; Berest, Dganit ; Gal, Meir ; Grobman, Mikhail ; Gershuni, Moshe ; David, Nurit ; Zonshine, Boaz ; Zonshine, Dana ; Sack, Daniel ; Yahav, Galia ; Yasour, Penny ; Cabessa, Miriam ; Cohen, Mirit ; Cohen Gan, Pinchas ; Luski, Aïm ; Mizrachi, Motti ; Matzliah, Tal ; Moshe, Dan ; Na'aman, Michael ; Ninio, Moshe ; Sun, Utah ; Sgan-Cohen, Michael ; Fainaru, Belo-Simion ; Frydlender, Barry ; Kupferman, Moshe ; Kadishman, Menashe ; Kantor, Zvika ; Katzenstein, uri ; Karavan, Dani ; Rosen, Roee ; Shirman, Simcha ; Shapira, Daphna
Anxiety, The Museum of Israeli Art, Ramat Gan, Opening: 1st September 1994. Art Focus Contemporary Israeli Art, Jerusalem 1994
boek